Investigations into the efficacy of a novel extubation-aerosol shield: a cough model study. Issue 1 (March 2022) - Hasegawa, Gen; Sakai, Wataru; Chaki, Tomohiro; Tachibana, Shunsuke; Kokita, Atsushi; Kato, Takenori; Nishimura, Hidekazu; Yamakage, Michiaki
Summary: Background: Physicians have had to perform numerous extubation procedures during the prolonged coronavirus disease 2019 (COVID 19) pandemic. Future pandemics caused by unknown pathogen may also present a risk of exposure to infectious droplets and aerosols. Aim: This study evaluated the ability of a newly developed aerosol barrier, "Extubation-Aerosol (EA)-Shield" to provide maximum protection from aerosol exposure during extubation via an aerosolised particle count and high-quality visualisation assessments. Methods: We employed a cough model having parameters similar to humans and used micron oil aerosol as well as titanium dioxide as aerosol tracers. Aerosol barrier techniques employing a face mask (group M) and EA-Shield (group H) were compared. Findings: The primary outcome was the difference in the number of particles contacting the physician's face before and after extubation. The maximum distances of aerosol dispersal after extubation were measured as the secondary outcomes. All aerosolised particles of the two tracers were significantly smaller in group H than in group M (p < 0.05). In addition, the sagittal and axial maximum distances and sagittal areas of aerosol dispersal for 3, 5, and 10 s after extubation were significantly smaller in group H than in group M (p < 0.05). Conclusion: This model indicates that EA-Shield could be highly effective in reducing aerosol exposure during extubation. Therefore, we recommend using it as an aerosol barrier when an infectious aerosol risk is suspected.